Characteristics of 1573 healthcare workers who underwent nasopharyngeal swab testing for SARS-CoV-2 in Milan, Lombardy, Italy. (October 2020) - Lombardi, A.; Consonni, D.; Carugno, M.; Bozzi, G.; Mangioni, D.; Muscatello, A.; Castelli, V.; Palomba, E.; Cantù, A.P.; Ceriotti, F.; Tiso, B.; Pesatori, A.C.; et al.
Abstract: Objectives: The management of healthcare workers (HCWs) exposed to confirmed cases of coronavirus disease 2019 (COVID-19) is still a matter of debate. We aimed to assess in this group the attack rate of asymptomatic carriers and the symptoms most frequently associated with infection. Methods: Occupational and clinical characteristics of HCWs who underwent nasopharyngeal swab testing for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a university hospital from 24 February 2020 to 31 March 2020 were collected. For those who tested positive and for those who tested positive but who were asymptomatic, we checked the laboratory and clinical data as of 22 May to calculate the time necessary for HCWs to then test negative and to verify whether symptoms developed thereafter. Frequencies of positive tests were compared according to selected variables using multivariable logistic regression models. Results: There were 139 positive tests (8.8%) among 1573 HCWs (95% confidence interval, 7.5–10.3), with a marked difference between symptomatic (122/503, 24.2%) and asymptomatic (17/1070, 1.6%) workers (p < 0.001). Physicians were the group with the highest frequency of positive tests (61/582, 10.5%), whereas clerical workers and technicians had the lowest frequency (5/137, 3.6%). The likelihood of testing positive for COVID-19 increased with the number of reported symptoms; the strongest predictors of test positivity were taste and smell alterations (odds ratio = 76.9) and fever (odds ratio = 9.12). The median time from first positive test to a negative test was 27 days (95% confidence interval, 24–30). Conclusions: HCWs can be infected with SARS-CoV-2 without displaying any symptoms. Among symptomatic HCWs, the key symptoms to guide diagnosis are taste and smell alterations and fever. A median of almost 4 weeks is necessary before nasopharyngeal swab test results are negative.